The exploratory study. My approach to the qualitative research world - Muñoz Aguirre, Nicanor Alonso (Investigación y Educación en Enfermería, 2011)
Accuracies and mistakes in the preparation of an exploratory study, in which coherence and viability of the future research is seen at the end, are shown. Ethical reflection is ruling in qualitative research, maximum when people involved in social conflict are involved, in which the researcher can be seen as an informer of the attacking group. The truth must be always present and reliable intersubjective relationships are essential.